Anxiety, sleep quality, and binge eating in overweight or obese adults - Benato Fusco, Suzimar de Fatima; Pires Amancio, Stefanie Cristina [UNESP]; Pancieri, Ana Paula [UNESP]; Faria Faddul Alves, Maria Virginia Martins [UNESP]; Spiri, Wilza Carla [UNESP]; Braga, Eliana Mara [UNESP] (Univ Sao Paolo, 2020)
Objective: To analyze the relationship of anxiety to binge eating and sleep quality in overweight or obese adults. Method: Transversal study, conducted between May 2015 and January 2017, with an intentional sample composed of literate individuals of both sexes, aged 20 to 59 years, who presented body mass index higher or equal to 25 kg/m(2). State Trait Anxiety Inventory, Binge Eating Scale, and Pittsburgh Sleep Quality Index were employed. Pearson or Spearman correlation coefficient was adopted for data analysis, according to its distribution. Results: The sample comprised 130 individuals. The overall and young adults' samples presented a positive correlation between anxiety and binge eating scores (p=0.0011) and sleep quality score (p=0.0081). Adults who were 45 or older presented an inverse relation between age and anxiety (p=0.0003). Conclusion: The overall sample and young adults who presented higher anxiety state had higher indexes of binge eating and a worse sleep quality, whereas for middle-aged adults, higher age was related to a lower anxiety score.
Keywords: Anxiety; Obesity; Overweight; Binge-Eating Disorder; Insomnia; Nursing Care